Cassava in the production of bread and bakery products - Omoaka, P.; Bokanga, M. (1994)
A significant proportion of wheat flour can be replaced by cassava flour in the making of bread with little changes in the quality of bread. This paper shows that it is possible to make bread without using wheat flour. Soybean flour can also be mixed with cassava flour to increase the protein content of the baked products. Recipes for making breads, cakes an biscuits from cassava flour, and bread from cassava starch are presented. Sensory evaluation tests show that all baked cassava products are highly acceptable to consumers.